Type I Takayasu’s arteritis: An unusual presentation in young female child - Sharma, B B; Sharma, Shashi; Sharma, Sandeep; Atwal, Swapndeep Singh; Sharma, Shweta (Indian Journal of Child Health, 2014)
Takayasu’s arteritis is a rare type of vasculitis of unknown origin in which aorta and its branches are affected. Aortoarteritis causes narrowing of vessel lumen due to inflammatory changes in the vessel wall which in turn leads to thrombus formation, occlusion, or both. However, very rarely these may present exclusively with facial palsy at the time of onset. We present such a rare case of young female child who reported to the outpatient department with unusual findings of facial palsy followed by stroke and was diagnosed as Type I Takayasu’s arteritis on the basis of various investigations. Magnetic resonance imaging and magnetic resonance angiography play a significant role in making the diagnosis.